Is renal biopsy always necessary to start immunosuppressive therapy in lupus nephritis? - Vasudevan Chelliah; V Balaraman; S Ilango; S Ramesh; V Kannan Bhaba; D Shivakumar (Indian Journal of Rheumatology)
Objective: Most of the patients with proliferative lupus nephritis (LN) have high titer of anti-dsDNA antibody and low complement levels. In this study, we tried to predict proliferative LN with serological profile. Methods: This prospective study was conducted in fifty pateints with known systemic lupus erythematosus (SLE) with laboratory evidence of LN (proteinuria, microscopic hematuria, or increased serum creatinine). Serological profile (anti-dsDNA, C3, and C4) and renal biopsy were done in all patients. Results: Of 50 patients, 35 had Class IV (70%), 7 Class II (14%), 4 Class V (8%), and 4 had Class IV and V (8%) on renal biopsy. Totally, 39 (78%) patients had proliferative LN (Class IV and Class IV and V). The prevalence of anti-dsDNA, low C3, and low C4 was 97.1%, 68%, and 74% with LN and 97.4%, 84.6%, and 87.2% with proliferative LN (P < 0.001), respectively. About 72% (28 of 39 patients) with proliferative LN had the combination of anti-dsDNA positivity, low C3, and low C4 levels. However, whoever had the combination of anti-dsDNA positivity, low C3, and low C4 showed only proliferative LN on biopsy. Positive predictive value was 100% (P < 0.05). None of the patients with Class II or Class V (nonproliferative LN) had this combination of serology. Conclusion: In this study, it was found that proliferative LN can be predicted by serological profile alone. Thus it might be argued that immunosuppressive therapy (steroids and mycophenolate mofetil) may be started without renal biopsy in a known SLE patient with laboratory evidence of LN and positive serology; however, robust studies are required.